DESAIN PENGELOLAAN KURIKULUM PESANTREN DAN PERGURUAN TINGGI BERBASIS KECERDASAN INTELEKTUAL DAN KECERDASAN SPIRITUAL - Abdul Chalim; Shohib Muslim; Sri Hudiarini; Fadloli (Bajang Institute, 2023)
This article discusses pesantren curriculum design in shaping the spiritual intelligence and intellectual intelligence of students. Based on the results of the study of primary sources, it can be concluded that student boarding schools make or design a curriculum based on curriculum management theory in general, starting from planning, organizing, actuating, and controlling/evaluating. This is seen as a necessity so that pesantren students can maximally give their role to students in developing their spiritual and intellectual mentality